2018
DOI: 10.1111/nep.13244
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinicopathologic observation in a case of steroid‐resistant nephrotic syndrome caused by a novel Crumbs homolog 2 mutation

Abstract: Recent advances in high-throughput sequencing for clinical genetic testing have revealed novel disease-causing genes, such as Crumbs homolog 2 (CRB2) for early-onset steroid-resistant nephrotic syndrome (SRNS). We report the long-term clinicopathologic observation of a Japanese female patient with SRNS caused by a newly identified compound heterozygous mutation of CRB2 (p.Arg628Cys and p.Gly839Trp located in the 10th and 11th epidermal growth factor-like domains, respectively). She was initially examined durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These data explore some of the mechanisms and impact of the relationship between CRB2 mutations and phagocytes to some extent. In 2018, Watanabe et al [ 14 ] showed a Japanese patient that her renal biopsy specimens in keeping with FSGS, a newly compound heterozygous mutation of CRB2, p.Arg628Cys and p.Gly839Trp located in the 10th and 11th epidermal growth factor-like domains, respectively. These results demonstrate that CRB2 mutations may also occur in Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…These data explore some of the mechanisms and impact of the relationship between CRB2 mutations and phagocytes to some extent. In 2018, Watanabe et al [ 14 ] showed a Japanese patient that her renal biopsy specimens in keeping with FSGS, a newly compound heterozygous mutation of CRB2, p.Arg628Cys and p.Gly839Trp located in the 10th and 11th epidermal growth factor-like domains, respectively. These results demonstrate that CRB2 mutations may also occur in Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…In human, while there is no known disease associated with CRB3 , both CRB1 and CRB2 bi-allelic pathogenic variations have been reported. CRB1 has been associated with retinal dystrophy including Leber’s congenital amaurosis and retinitis pigmentosa [ 9 ], whereas CRB2 variations are responsible for a wide phenotypic spectrum ranging from a severe prenatal disease with severe renal anomalies variably associated with hydrocephalus to postnatal isolated renal anomalies, with only few cases with retinal involvement [ 10 18 ]. To date, 34 cases with CRB2 bi-allelic variations have been reported, including many cases with hydrocephalus, but, partly because this gene was first considered as causal for renal abnormalities, no neuropathological characterization has been performed until now.…”
Section: Introductionmentioning
confidence: 99%